Mormons & cowboys, moonshiners & Klansmen : federal law enforcement in the South & West, 1870-1893 - Cresswell, Stephen Edward (University of Alabama Press, 1991)
In the decades immediately following the Civil War, the United States expanded rapidly. As the nation grew, so too did federal law, moving into areas of citizens' lives previously regulated by local custom and state and territorial statutes. In Mormons and Cowboys, Moonshiners and Klansmen, Cresswell uses then moves beyond a case-study approach to illuminate larger questions including the evolution of the American criminal justice system, the relationship of the South and the West to the rest of the nation, the workings of the 19th-century American bureaucracy, and conflict of the local, state,